ANALISIS TATA KELOLA DATA OLEH OFFICE ADMINISTRATIVE MANAGER DI PT X - Nurun Nazwa Meynanda; Christian Wiradendi Wolor; Eka Dewi Utari (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This research aims to analyze the data governance implemented by the Office Administration Manager at PT X and provide strategic recommendations to improve the effectiveness and efficiency of data management. This research uses a descriptive approach with a qualitative case study method. Data was collected through in-depth interviews, direct observation, and review of relevant documents. The results showed that PT X has made the transition from a manual system to a digital system, but data management policy updates have not been carried out in a structured and regular manner. The application used has not been optimized due to limited automatic backup features, change tracking, and dependence on simple software. In terms of security, some data has not been thoroughly encrypted and there is no audit trail system available. Therefore, PT X is advised to develop a targeted update policy, improve employee digital literacy, and strengthen information security to support decision-making and operational sustainability.